Emissões veiculares: uma abordagem rápida e eficiente para a determinação de H2, CO, CH4 e CO2 por GC-BID e de BTEX por SPME-GC-BID - Souza, Francisco Thiago Correia de (2025)
The combustion of fossil fuels is a predominant source of air pollutants. BTEX (benzene, toluene, ethylbenzene, and xylenes) and the gases CO, CH4 and CO2 are known to have negative impacts on human health and the environment. Given the technical challenges associated with sampling, sample preparation, and analysis for quantifying these compounds in exhaust gases, this study developed analytical methods to mitigate these limitations. Exhaust gas samples from a motorcycle in idle mode were collected using 1.0 L sampling bags, integrated with a newly designed sampling device specifically developed for gas analysis in this study. The quantification of H2, CO, CH4 and CO2 was performed without the need for sample preparation, by directly transferring 0.1 mL of the sampled gas for analysis using gas chromatography (GC) coupled with a barrier discharge ionization detector (BID). For BTEX quantification, solid-phase microextraction (SPME) was employed using a 75 μm CAR/PDMS fiber, combined with GC-BID. The method validation for BTEX demonstrated selectivity, with limits of detection (LOD) ranging from 4.49×10⁻2 to 7.88×10⁻2 ppmv, limits of quantification (LOQ) from 1.36×10⁻1 to 2.38×10⁻1 ppmv, precision between 1.47 % and 7.14 %, and recovery rates from 82.3 % to 109 %. The concentration of BTEX in vehicle exhaust gas ranged from 7.91×10⁻1 ± 3.36×10⁻2 to 4.37 ± 7.39×10⁻2 ppmv. For H2, CO, CH4 and CO2, the method exhibited selectivity, with LOD values ranging from 63.9 to 115 ppmv, LOQ values from 194 to 348 ppmv, precision between 1.27 % and 6.22 %, and recovery rates from 90.8 % to 102 %. The concentrations of these gases at the exhaust outlet varied from 870 ± 5.98×101 to 1.06×105 ± 7.77×101 ppmv. These results highlight the relevance of the developed methods in improving vehicle emissions monitoring, providing precise analytical tools. These tools can support public policies aimed at reducing air pollution, contributing to environmental preservation and public health promotion.